Manajemen Keuangan Berbasis Investasi Pasar Modal Atlet Judo di Wonogiri - Kuncoro, Trian Gigih; Santi Putriani; Handy Nugraha; Firdaus Kurniawan (Universitas Muhammadiyah Surakarta, 2024)
During their productive years, athletes can earn incomes above the per capita average of a country or region. However, upon retirement, athletes often face financial problems, as many professional athletes lack the skills to effectively manage personal finances. Their occupation, which heavily relies on physical strength, makes their finances vulnerable. Additionally, professional athletes are prone to mental health issues and excessive anxiety or depression. Some athletes even commit suicide after retiring. The presence of these risks forces many athletes to retire at a relatively young age, around their 30s, and they may struggle to find suitable post- athletic careers. Hence, athletes need to plan their finances for a longer period compared to most people. Unstable incomes during their sports careers, often dependent on sponsorships, prizes, and awards, make them vulnerable to income declines after retirement. Moreover, high expenses during their careers, especially for training and medical care, might not have allowed them to build substantial savings. Researchers argue that financial literacy and security enable athletes to ensure their financial well-being, particularly in their post-athletic lives. Financial literacy can help athletes achieve sustainable financial well-being. Financial planning before retirement is crucial for individuals or families to achieve stable and prosperous financial conditions. Interviews we conducted found that all athletes at Dojo Judo Gajah Mungkur have goals for the money earned from competitions. However, only a few, especially the younger ones, use their income productively. This is evidenced by initial interviews showing that most of them, or 50-70 percent, spend their income on purchasing motor vehicles, and 80 percent of athletes do not have businesses or investments (both in the real and non-real sectors) that can generate additional income outside their profession.